Concertive resistance: how overlapping team identifications enable collective organizational resistance. Issue 3 (3rd May 2020) - Zanin, Alaina C.; Bisel, Ryan S.
ABSTRACT: This study describes how overlapping sources of identification allow organizational members to resist managerial influence collectively in the absence of overt talk or leadership communication – labeled here concertive resistance . Concertive resistance is exercised by organizational members according to a set of core group-level values which challenge, invert, or disrupt top-down control. Concertive resistance extends Barker's [1993. "Tightening the Iron Cage: Concertive Control in Self-managing Teams." Administrative Science Quarterly 38 (3): 408–437] concept of concertive control by explaining how team-level resistance is also attributable to team-level control. Through an ethnography of an American university football team, this study reveals how multiple and overlapping sources of identification produced a team's spontaneously and collective resistance, without the aid of overt resistance leadership. The essay contributes to the resistance literature by using Unobtrusive Control Theory to explain how group-level resistance is accomplished through control.